2007
DOI: 10.1088/0953-4075/40/19/013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the free ion Nd3+spectrum (Nd IV)

Abstract: A recent breakthrough in the analysis of Nd IV resulted in the establishment of 37 energy levels of the ground configuration 4f3. We report here the completion to all 41 levels of this configuration. Wavelength measurements extended to 2800 Å and in higher excitation conditions lead to the classification of 1426 lines involving the excited configurations 4f25d, 4f26p, 4f26s. Owing to configuration mixing between 5p64f26p and the core-excited 5p54f4, numerous 5p64f25d–5p54f4 transitions, normally dipole-forbidd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 21 publications
6
63
1
Order By: Relevance
“…For electric dipole transitions, our results are expected to be more accurate than those previously published in view of the much more extended amount of electronic correlation effects (including core-excited correlation) considered in our physical model. In the case of magnetic dipole and electric quadrupole lines, our results have been found to be in good agreement with theoretical data recently published for the most intense transitions [164].…”
Section: Lanthanide Elementssupporting
confidence: 92%
“…For electric dipole transitions, our results are expected to be more accurate than those previously published in view of the much more extended amount of electronic correlation effects (including core-excited correlation) considered in our physical model. In the case of magnetic dipole and electric quadrupole lines, our results have been found to be in good agreement with theoretical data recently published for the most intense transitions [164].…”
Section: Lanthanide Elementssupporting
confidence: 92%
“…The results presented in this table are limited to transitions for which log gf is greater than −1.0. To our knowledge, prior to our work, transition probabilities in Nd IV were only published by Wyart et al (2007) who also used the HFR method combined with parametric least-squares fits but including a rather limited set of interacting configurations, i.e. figure 2, showing a general good agreement (within 25%) between both sets of data.…”
Section: Electric Dipole Transitionsmentioning
confidence: 94%
“…This picture is no more valid in the case of Nd 3+ due to the fact that some core-excited configurations with an open 5p subshell are expected to strongly interact with lower configurations. More precisely, in their analysis of the Nd IV spectrum, Wyart et al (2007) showed that, owing to configuration mixing between 5p 6 4f 2 6p and the core-excited 5p 5 4f 4 , numerous 5p 6 4f 2 5d-5p 5 4f 4 transitions, normally dipole-forbidden, were observed experimentally. They also showed that the addition of the 5p 5 4f 3 5d configuration (still unknown) to 5p 6 4f 2 (5d+6s) in a three-configuration basis improved significantly the calculated energies in 4f 2 5d and 4f 2 6s configurations and reduced the transition probabilities for 5p 6 4f 3 -5p 6 4f 2 5d by a factor of about 2.…”
Section: Relativistic Hartree-fock Calculationsmentioning
confidence: 99%
“…It is interesting to note, that in spite of obvious disadvantages of the iterative method (the problems of convergence and lack of the covariance matrix (see p.6 in [42]), its usage can be met in current publications (see e.g. [43]). …”
Section: Introductionmentioning
confidence: 99%